Valorization of textile industry shearing waste via biochar production: An environmentally friendly energy resource - Aljomah, Abdul Karim; Kardas, Elif; Tasar, Seyda; Yilgin, Melek (Pergamon-Elsevier Science Ltd, 2025)
Traditional disposal methods for textile waste, including incineration and landfilling, pose serious environmental risks due to the release of CO2, volatile organic compounds, and microplastics. Unlike most previous studies that focused on biomass or single-fiber residues, this work targets non-recyclable cotton/polyester shearing waste--an industrial by-product typically excluded from conventional recycling streams. The study explores the valorization of this mixed-fiber waste through torrefaction for biochar production and evaluates its potential as a sustainable solid fuel. Torrefaction experiments were performed at seven temperatures (225-375 degrees C) and four residence times (1-4 h) under a nitrogen atmosphere to investigate how process conditions affect product yield and fuel properties. The biochar yield decreased from 71.6 % at 225 degrees C to 18.3 % at 375 degrees C, while the carbon content increased from 58.2 % to 75.9 %, and the higher heating value (HHV) improved from 20.4 MJ kg-1 to 31.6 MJ kg-1. The optimal sample (SW350-4) exhibited a combustion reactivity of 0.8358 mu g min-1 K-1, comparable to lignite, with low ash (1.8 wt%) and sulfur (0.04 wt%) contents, confirming its high stability and clean-burning nature. FTIR analysis revealed the removal of hydroxyl and aliphatic groups and the development of aromatic carbon structures, indicating progressive carbonization at elevated temperatures. Overall, the study provides new insight into the thermochemical conversion behavior of mixed cotton/polyester textile waste and demonstrates its feasibility as a low-emission, high-energy solid fuel. The findings support sustainable waste management and contribute to circular economy goals and clean energy transition strategies.
Keywords: Shearing waste; Torrefaction; Biochar; Thermogravimetric analysis; Combustion performance; Sustainable energy